The Moderating Effect of Religiosity on Halal Certification Among Food Manufacturers in Malaysia - Risyawati Mohamed Ismail; Sitti Aminah Baharuddin; Saroja Devi Neyson Dorai; Abd.Ramli Romle; Siti Norhasmaedayu Mohd Zamani (International Journal of Supply Chain Management, 2020)
Halal compliance is very crucial for halal certified food manufacturers. However, over time, there are many cases of non-compliances which resulted in the revocation of halal certificate among Malaysian food and beverage manufacturers. This study looked at the role of religiosity in ensuring halal compliance in companies operating in Malaysia. Results from the quantitative analyses indicated that religiosity did not have an impact on halal compliance by Malaysia FB companies. This conclusion indicated that the existing Malaysia halal management system might be the main factor which ensure compliance among FB stake holders in Malaysia.